THE RELATIONSHIP BETWEEN IQ, LEARNING MOTIVATION AND LEARNING FACILITIES UTILIZATION WITH BIOLOGY COGNITIVE LEARNING ACHIEVEMENT OF THE FIRST GRADE STUDENTS OF SMA NEGERI 7 SURAKARTA - Ratih Dewi Puspitasari; PUGUH KARYANTO; Slamet Santosa (Bioedukasi: Jurnal Pendidikan Biologi, 2012)
The aims of this research were to know the relationship between : 1) IQ with biology cognitive learning achievement of the first grade students, 2) learning motivation with biology cognitive learning achievement of the first grade students, 3) learning facilities utilization with biology cognitive learning achievement of the first grade stu- dents.This was a correlational research. The population were all of the first grade students of SMAN 7 Surakarta in academic year of 2011/2012. The sample was taken among 80 samples of student using simple random sampling technique. Documentation method was used to uncover student’s cognitive learning achievement, IQ was measured by test, while learning motivation and learning facilities utilization was measured by questionnaire. The obtained data was analysed using multiple regression analysis of SPSS 17. The result showed that there was a significant and positive correlation between learning motivation with biology cognitive learning achievement of the first grade students of SMAN 7 Surakarta, with relative contribution was 100% and efective contribution was 6,8%. The previous research showed that there were a significant and positive correlation between IQ and learning facilities utilization with student’s achievement, but in this research there were not a significant correlation both IQ and learning facilities utilization with biology cognitive learning achievement of the first grade students of SMAN 7 Surakarta.